The Effect of Hypoxia-Inducible Factors Levels in Sera of Babylon Women with Breast Cancer - Sheerin H. Abbas; Zinah Abbass Ali; Alaa Sadiq Alaawad (Medical Journal of Babylon)
Background: The most common cause of death linked to advanced stages of breast cancer (BC) is metastases. Newly, biomarkers of tumors are important due to their probable use in the early detection of the tumor. Many types of cancer were associated with hypoxia. The action of the hypoxia-inducible factors (HIFs), the component of the response to hypoxia and its adaptive, improves cancer complications like immune suppression, disturbed metabolism, angiogenesis, invasive, and metastasis. HIFs became important aim in anticancer therapy designation. Objectives: The aim of the present education is to evaluate HIF 1α (HIF-1A) and HIF 2α (HIF-2A) levels in the plasma of Babylon women with BC and control groups. Materials and Methods: The case–control group was made up of 50 women (presumably healthy women), whereas the sick group was made up of 50 women with BC. In plasma, the concentrations of HIF-1α (HIF-1A) and HIF-2α (HIF-2A) levels were evaluated by enzyme-linked immunosorbent assay (ELISA), and the statistical analysis was conducted by the SPSS software. Results: The results showed elevated HIF-1A and HIF-2A levels in the patient’s group compared with the control group (P < 0.05). Conclusion: The women with BC had elevated serum levels of HIF-1A and HIF-2A. Based on the results of this investigation, indicate the role of HIF-1A and HIF-2A as prognostic indicators in BC women.